Transfusion policy after severe postpartum haemorrhage: a randomised non‐inferiority trial. (10th January 2014) - Prick, BW; Jansen, AJG; Steegers, EAP; Hop, WCJ; Essink‐Bot, ML; Uyl‐de Groot, CA; Akerboom, BMC; van Alphen, M; Bloemenkamp, KWM; Boers, KE; Bremer, HA; Kwee, A; et al.
<x xml:space="preserve">Abstract</x> Objective To assess the effect of red blood cell (RBC) transfusion on quality of life in acutely anaemic women after postpartum haemorrhage. Design Randomised non‐inferiority trial. Setting Thirty‐seven Dutch university and general hospitals. Population Women with acute anaemia (haemoglobin 4.8–7.9 g/dl [3.0–4.9 mmol/l] 12–24 hours postpartum) without severe anaemic symptoms or severe comorbidities. Methods Women were allocated to RBC transfusion or non‐intervention. Main outcome measures Primary outcome was physical fatigue 3 days postpartum (Multidimensional Fatigue Inventory, scale 4–20; 20 represents maximal fatigue). Non‐inferiority was demonstrated if the physical fatigue difference between study arms was maximal 1.3. Secondary outcomes were health‐related quality of life and physical complications. Health‐related quality of life questionnaires were completed at five time‐points until 6 weeks postpartum. Results In all, 521 women were randomised to non‐intervention (n = 262) or RBC transfusion (n = 259). Mean physical fatigue score at day 3 postpartum, adjusted for baseline and mode of delivery, was 0.8 lower in the RBC transfusion arm (95% confidence interval: 0.1–1.5, P = 0.02) and at 1 week postpartum was 1.06 lower (95% confidence interval: 0.3–1.8, P = 0.01). A median of two RBC units was transfused in the RBC transfusion arm. In the non‐intervention arm, 33 women received RBC transfusion, mainly because of anaemic symptoms. Physical complications were comparable. Conclusions Statistically, non‐inferiority could not be demonstrated as the confidence interval crossed the non‐inferiority boundary. Nevertheless, with only a small difference in physical fatigue and no differences in secondary outcomes, implementation of restrictive management seems clinically justified.